ALL IN GOOD TASTE: SAVOR THE FLAVORS OF TAIWANSEBAGAI UPAYAPELAKSANAAN NATION BRANDINGTAIWAN - Rahayu Dian Sari, Ni Luh Putu; Kumala Dewi, Putu Ratih; Prameswari, A.A. Ayu Intan (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2020)
ABSTRACT   This research is conducted with qualitative research method to compile how Taiwan conducted their gastrodiplomacy program named All in Good Taste: Savor The Flavors of Taiwan as a way to brand the country . Taiwan used several ways to promote the program, including two major strategies, namely the Internationalization Strategy and the International Localization Strategy which lasted until 2013as a tool to show the country’s existence and also to introduce Taiwan's culinary culture. Taiwan conducted the said program as a brand to achieve various goals, including building an image, enhancing the nation's competitiveness, and forming the identity with various cultures and ethnics . Although the impact of the nation branding according to NBI could not be seen properly , and the results obtained from gastrodiplomacy can not be achieved directly,the Taiwanese cuisine was slowly gaining recognition by public .                                                   Keywords: Gastrodiplomacy, Nation Branding, Taiwan